E-015 Beyond the wall: imaging of perivascular structures of the intracranial subarachoid space. (4th August 2020) - Anagnostakou, V; Vardar, Z; Puri, A; Ughi, G; Gounis, M
Abstract : Introduction: A new method of intravascular imaging is introduced, high-frequency optical coherence tomography (HF-OCT), with resolution unprecedented for in vivo imaging (~10µm). Here we describe the first preclinical observations of cerebrovascular imaging with this new technology. Methods: Two dogs were imaged using HF-OCT. A 6F straight guiding catheter was initially positioned into the right vertebral artery up to the origin of the right lateral spinal ramus anastomoticus and the basilar artery was accessed with an SL-10 microcatheter. In the first dog access was achieved through the main lumen of the vertebral artery coursing along the vertebral column around the C1 vertebral body and finally the vertebrobasilar junction and the basilar artery. In the second dog access was achieved through the right lateral spinal ramus and the anterior spinal artery, the diamond shaped confluence of anastomotic channels between vertebral arteries and spinal rami into the basilar artery. In both animals the microcatheter was advanced up to the P1-P2 segment of the left PCA in order to facilitate positioning of the HF-OCT wire which was unsheathed from the microcatheter. Using contrast at a flow rate of 4 ml/sec to wash out the blood in the vessels imaging of the basilar artery from distal to proximal was performed. Results: Detailed images of the basilar artery, lower cerebellar arteries, basilar perforators, vertebrobasilar junction, spinal perforators were obtained (figure 1 ). Due to the high resolution of the method, the layers of the vessel wall were imaged. What was even more interesting was the ability to image beyond the artery into the structural components of the subarachnoid space with the arachnoid membranes and what we believe to be the arachnoid trabeculae. Venous structures and nerve root origins were also recognized. Conclusion: HF-OCT imaging can offer detailed visualization not only of the vessel wall, the branching pattern of basilar and spinal perforators but also of structures of the subarachnoid space impossible to study with other imaging modalities due to inadequate resolution. The clinical implication of such an analysis is yet to be discovered. Disclosures: V. Anagnostakou: None. Z. Vardar: None. A. Puri: None. G. Ughi: None. M. Gounis: None.